2021
DOI: 10.1371/journal.pntd.0009860
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent circulation of dengue serotype 1, 2 and 3 among acute febrile patients in Cameroon

Abstract: Acute febrile patients presenting at hospitals in Douala, Cameroon between July and December 2020, were screened for dengue infections using RT-PCR on fragments of the 5’ and 3’ UTR genomic regions. In total, 12.8% (41/320) of cases examined were positive for dengue. Dengue virus 3 (DENV-3) was the most common serotype found (68.3%), followed by DENV-2 (19.5%) and DENV-1 (4.9%). Co-infections of DENV-3 and DENV-2 were found in 3 cases. Jaundice and headache were the most frequent clinical signs associated with… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 51 publications
1
22
1
Order By: Relevance
“…The peto’s odds ratio [46] was used to pool the odds ratio of individual studies. In our meta-analysis (Figure 5), cross-sectional studies in Cameroon [30, 45], and Kenya [22] revealed significantly lower odds of co-infection in contrast with the absence of acute dengue infections (OR: 0.60; 95% CI, 0.42 – 0.87). Cross-sectional studies in Nigeria [16, 18, 20, 25, 32, 33, 35], Tanzania [17], Sierra Leone [23], Democratic Republic of Congo (DRC) [34], Cameroon [31], Sudan [40, 42], and Senegal [21] indicated no significant odds of co-infection in comparison with acute dengue negatives (OR = 1.07; 95% CI = 0.58, 1.94).…”
Section: Resultsmentioning
confidence: 77%
See 2 more Smart Citations
“…The peto’s odds ratio [46] was used to pool the odds ratio of individual studies. In our meta-analysis (Figure 5), cross-sectional studies in Cameroon [30, 45], and Kenya [22] revealed significantly lower odds of co-infection in contrast with the absence of acute dengue infections (OR: 0.60; 95% CI, 0.42 – 0.87). Cross-sectional studies in Nigeria [16, 18, 20, 25, 32, 33, 35], Tanzania [17], Sierra Leone [23], Democratic Republic of Congo (DRC) [34], Cameroon [31], Sudan [40, 42], and Senegal [21] indicated no significant odds of co-infection in comparison with acute dengue negatives (OR = 1.07; 95% CI = 0.58, 1.94).…”
Section: Resultsmentioning
confidence: 77%
“…A total of 3942 records were identified during literature retrieval from the databases. A total of 30 studies from (sub-Saharan) Africa involving 25,241 febrile patients were included in this meta-analysis [15-45] (Figure 10, Table 1). The quality score of the included studies ranged from 4 to 7 on a maximum scale of quality scores of 8 for case reports, 9 for cross-sectional studies, and 11 for case-control studies using the JBI criteria (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[18][19][20][21] The DENV-2 is one of the most common serotype speeding throughout the world. 22 The aim of this study is to compare and screen out the best in-house acridinedione (DSPD1-DSPD6) molecules with the best reported cocrystallized ST-148 inhibitor of DENV-2 C protein. The DSPD molecules (DSPD1-DSPD6) were synthesized by the microwave-aided green procedures mediated by solvent-free silica irradiation from ethyl-3-(2,4-dioxocyclohexyl) propanoate and various amines by in situ products of β-enaminoester.…”
Section: Introductionmentioning
confidence: 99%
“…Many drug molecules have reached clinical trials, but none of them were effective against DENV complications 18–21 . The DENV‐2 is one of the most common serotype speeding throughout the world 22 . The aim of this study is to compare and screen out the best in‐house acridinedione (DSPD1–DSPD6) molecules with the best reported cocrystallized ST‐148 inhibitor of DENV‐2 C protein.…”
Section: Introductionmentioning
confidence: 99%